Análisis de satisfacción al cliente del Banco General Rumiñahui en relación a sus servicios en la ciudad de Machala - Parrales Mayorga, Mercedes Elizabeth (2015)
The work presented, aims to analyze the levels of customer satisfaction BGR in relation to their services in the city of Machala, It is its overall objective: Determine the analysis of customer satisfaction with the services offered by BGR Machala. And their specific objectives: To identify the degree of customer satisfaction in relation to services, identifying factors influencing the quality of service and establish the perception that customers in relation to services. His research methodology was explorative way, through surveys for market research. To determine the population PEA (economically active population) was taken, getting 398 as shown. Among the most important findings it is that they could identify the most important attributes for the customer and where to direct efforts to maintain service quality, besides raising strategies aimed at improving communication between internal and external customer. It is recommended to seize opportunities to introduce new promotions to attract customers by improving the relationship between client and agency BGR Machala it is also recommended that all staff use the service protocols to increase the level of customer satisfaction.